University Students’ Perception of Demotivating Factors in Learning English as a Foreign Language - Nafiseh Hosseinpour (Journal of Applied Linguistics, 2013)
Demotivation is a relatively new topic in the field of second or foreign language acquisition which is in need of more rigorous research. In this regard, the present study was an attempt to investigate demotivating factors in learning English as a foreign language in an Iranian context. To this end, 382 Persian learners of English were selected through stratified clustering sampling procedure to participate in this mixed method study. The Data was collected through a 40-item Likert type questionnaire. The Factor analysis of the data extracted seven factors including a) inadequate facilities, b) reduced self-confidence, c) class characteristics, d) lack of purpose to study English, e) teaching methods, f) teachers and teaching styles, and g) negative attitudes toward English and the culture of English-speaking countries as demotivators. The Students’ perceptions of these seven factors were compared based on their general English proficiency levels. The Results revealed that low proficient learners perceived reduced self-confidence and negative attitudes more demotivating than their counterparts at other levels of proficiency.